Kontinuitas dan Transformasi Sistem Pendidikan Pesantren: Studi Historis Pendidikan Dinasti Abbasiyah (750-1258 M) dan Relevansinya bagi Pendidikan Islam Kontemporer - Ahmad Sayyidiman Hamidalloh; M. Syafrany Surya Permadi; Dafa Aqila Musyaffa; Mohammad Hakim Alfarisi (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2026)
This study aims to analyze the continuity and transformation of the Islamic boarding school (pesantren) education system through a historical study of Islamic education during the Abbasid Dynasty and to examine its relevance in the context of contemporary Islamic education. This study uses a qualitative approach with library research, integrating historical and analytical-critical approaches. Data were obtained from relevant primary and secondary literature, then analyzed using content analysis and interpretative techniques. The results show that the Abbasid education system has a fundamental role as the historical foundation of Islamic education, especially in the aspects of the integration of science, institutions, and intellectual traditions. In the context of Islamic boarding schools, there is continuity in aspects of learning methodology, scientific authority, and the use of classical texts, which are inherited through a process of adaptation and contextualization. On the other hand, Islamic boarding schools also experienced transformations in aspects of institutions, curriculum, and learning methods in response to the dynamics of modernity. The main findings of this study confirm that the relationship between continuity and transformation is dialectical, where both complement each other in forming a dynamic education system. The implications of this study demonstrate the importance of developing an integrative Islamic education model, balancing the preservation of tradition and innovation.